Diversity of keratinophilic mycoflora in the soil of Agra (India) - Saxena, P; Kumar, A; Shrivastava, J N (Folia microbiologica, 2004)
Diversity of keratinophilic mycoflora in the soil of Agra was under observation for 1 year (July 2001-June 2002) and isolation of keratinophilic fungi was followed by the hair-baiting method. The frequency of occurrence of keratinophilic fungi in 284 soil samples collected from various hospitals, cattle yards, poultry farms, crop fields and playgrounds was determined, 204 samples (72%) having been found to be positive. A total of 33 species classified into 11 genera (Acremonium, Aspergillus, Chrysosporium, Emmonsia, Geomyces, Keratinophyton, Microsporum, Myceliophthora, Penicillium, Sporotrichum, Trichophyton) were encountered from the soil samples. Sporotrichum spp. were found to be the most dominant species followed by Trichophyton simii. The parameter of keratinophilic fungi found in the samples studied ranged from 62 to 80% where playgrounds yielded the maximum number of species (80%) while the least dominating soil was hospital soil (62%). Among all the baits used maximum fungi occurred on human hairs (82%) followed by chicken feather (74%), wool (61%) and the least on horns (45%). The spectrum of keratinophilic fungi isolated from different sites differed considerably according to the frequency of use by humans.
Keywords: houby; Seasons; Soil Microbiology; půdní mikrobiologie; Fungi; roční období